Maternal urinary levels of glyphosate during pregnancy and anogenital distance in newborns in a US multicenter pregnancy cohort. (1st July 2021) - Lesseur, Corina; Pirrotte, Patrick; Pathak, Khyatiben V.; Manservisi, Fabiana; Mandrioli, Daniele; Belpoggi, Fiorella; Panzacchi, Simona; Li, Qian; Barrett, Emily S.; Nguyen, Ruby H.N.; Sathyanarayana, Sheela; Swan, Shanna H.; et al.
Abstract: Human exposure to glyphosate has become ubiquitous because of its increasing agricultural use. Recent studies suggest endocrine disrupting effects of glyphosate. Specifically, in our work in rodents, low-dose early-life exposure to Roundup® (glyphosate-based herbicide) lengthened anogenital distance (AGD) in male and female offspring. AGD is a marker of the prenatal hormone milieu in rodents and humans. The relationship between glyphosate exposure and AGD has not been studied in humans. We conducted a pilot study in 94 mother-infant pairs (45 female and 49 male) from The Infant Development and the Environment Study (TIDES). For each infant, two AGD measurements were collected after birth; the anopenile (AGD-AP) and anoscrotal (AGD-AS) distances for males, and anoclitoral (AGD-AC) and anofourchette distances (AGD-AF) for females. We measured levels of glyphosate and its degradation product aminomethylphosphonic acid (AMPA) in 2nd trimester maternal urine samples using ultra-high-performance liquid chromatography-tandem mass spectrometry. We assessed the relationship between exposure and AGD using sex-stratified multivariable linear regression models. Glyphosate and AMPA were detected in 95% and 93% of the samples (median 0.22 ng/mL and 0.14 ng/mL, respectively). Their concentrations were moderately correlated (r = 0.55, p  = 5.7 × 10 −9 ). In female infants, high maternal urinary glyphosate (above the median) was associated with longer AGD-AC (β = 1.48, 95%CI (−0.01, 3.0), p  = 0.05), but this was not significant after covariate adjustment. Increased AMPA was associated with longer AGD-AF (β = 1.96, 95%CI (0.44, 3.5), p  = 0.01) after adjusting for infant size and age at AGD exam. No associations were detected in male offspring. These preliminary findings partially reproduce our previous results in rodents and suggest that glyphosate is a sex-specific endocrine disruptor with androgenic effects in humans. Given the increasing glyphosate exposures in the US population, larger studies should evaluate potential developmental effects on endocrine and reproductive systems. Graphical abstract: Image 1 Highlights: Glyphosate-based herbicides are widely used worldwide. Glyphosate and AMPA detected in >90% of 2nd trimester maternal urine samples. High maternal glyphosate/AMPA associated with longer female anogenital distance. Glyphosate could act as a sex-specific endocrine disruptor.